The pharmacodynamics and pharmacokenetics of rectal administration of artesunate in the initial treatment of moderately severe and severe malaria in South African adults in northern Kwazulu Natal - Barnes, Karen I (Division of Clinical Pharmacology, 2014)
Includes bibliographical references.